IMPLEMENTASI MODEL PDEODE BERBANTUAN PhET UNTUK MEREMEDIASI MISKONSEPSI SISWA PADA KONSEP RANGKAIAN LISTRIK ARUS SEARAH - Cahyanto, Andi Dwi; Sitompul, Stepanus Sahala; Mursyid, Sukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis pre-experimental study aims to know the effectiveness of remediation on students’ misconceptions by using PDEODE learning model aided PhET on the concept of direct-current electrical circuit to students of grade XI IPA I SMA Negeri 1 Sintang. 27 students in XI grade was selected by intact group in random sampling technique as a sample of this research. A diagnostic test consist of 8 multiple choice questions with an open reason is used as a research instrument to find students' misconceptions. The instrument was tested in MA Negeri Sintang and obtained index reliability 0.711 which as reliable categories. Based on the results, the highest percentage of students’ misconceptions during pretest (85.19%) and posttest (37.04%) is on the concept of effect of adding or reducing a lamp to another bright flame of light on parallel circuit. Overall, average decrease of students’ misconceptions each indicator is 63.55%. The effectiveness of remediation is shown from the magnitude of effect size value with the result of 2.18 which was high categorized. This research is expected to be an alternative choice for teacher to reduce students’ misconceptions.Keywords: Remediation, Miconception, Effectiveness, PDEODE, PhET, Direct-Current Electrical Circuit